The effect of “moderately restricted carbohydrate” diet on gut microbiota composition and metabolic parameters in women with metabolic syndrome: a study protocol for a randomized controlled trial - Seyed Mohammad Mousavi; Hanieh-Sadat Ejtahed; Hanieh Malmir; Seyed Davar Siadat; Shirin Hasani-Ranjbar; Bagher Larijani; Ahmad Esmaillzadeh (Trials, 2022)
Abstract Background Metabolic syndrome (MetS) is a group of risk factors that increase the risk of death and a variety of chronic diseases. Recent studies have indicated that the imbalance of gut microbiota might contribute to development and progression of metabolic syndrome. Carbohydrate restriction in the diet has been proven to be one of the most effective methods in the management of metabolic syndrome, even in the absence of weight loss. However, no study has examined the effects of a carbohydrate-restricted diet on gut microbiota composition in metabolic syndrome patients. Thus, we will examine the effects of a “moderately restricted carbohydrate (MRC)” diet on gut microbiota, insulin resistance, and components of MetS among Iranian women. In addition, the stability of changes in dependent variables, including gut microbiota, will also be assessed. Methods This is a parallel randomized clinical trial in which 70 overweight or obese women aged 20–50 years with MetS will be randomly assigned to receive either MRC diet (42–45% carbohydrate, 35–40% fats) or a normal weight loss (NWL) diet (52–55% carbohydrate, 25–30% fats) for 3 months. Protein accounted for 15–17% of total energy in both diets. The quantity of gut microbiota including Firmicutes, Bacteroidetes, Bifidobacteria, Lactobacillus, Clostridium, Prevotella, Bacteroidetes, and Akkermansia muciniphila, as well as anthropometric, blood pressure, and metabolic parameters will be measured at study baseline and the end of trail. At the end of this phase, all participants will be placed on a weight maintenance diet for an additional 6 months. After following up study subjects in this duration, all dependent variables will be examined again to assess their stability over this period. Discussion To the best of our knowledge, this is the first randomized controlled trial investigating the effects of a moderately restricted carbohydrate diet on gut microbiota composition and several metabolic parameters during the weight loss and maintenance phases in women with MetS. Trial registration Iranian Registry of Clinical Trials ( www.irct.ir , IRCT20210307050621N1). Registered on May 31, 2021.